The billionaire's secret marriage eaudiobook - Dearen, Tamie (Limitless Sweet Billionaire Romance, 2020)
Stephanie Caldwell made the worst mistake of her life . . . she fell in love with her boss. Steph doesn't care that Bran is totally blind—at least he'll never notice the longing looks she gives him. If only she could warn him about the lack of love on his conniving fiancée's face. But Steph has to keep her mouth shut, or she could lose her job, along with the health insurance that keeps her daughter alive. Billionaire Branson Knight knows women regard him as a pitiful blind man, his wealth his only attraction. So his engagement is merely a means to an end. But the last thing he wants to end is his relationship with Stephanie—he depends way too much on his efficient personal assistant. Can Stephanie stand by while Bran's devious fiancée coerces him into a quickie marriage? Or will she lose her temper . . . and everything else along with it?